Treatment Trends and Outcomes in Healthcare‐Associated Pneumonia. Issue 11 (1st November 2017) - Haessler, Sarah; Lagu, Tara; Lindenauer, Peter K.; Skiest, Daniel J.; Priya, Aruna; Pekow, Penelope S.; Zilberberg, Marya D.; Higgins, Thomas L.; Rothberg, Michael B.
Abstract : BACKGROUND: The American Thoracic Society and Infectious Diseases Society of America guidelines for management of healthcare‐associated pneumonia (HCAP), first published in 2005, have been controversial regarding the selection of empiric broad‐spectrum antibiotics, whether the criteria for HCAP predicts the likelihood of infection with multidrug resistant organisms, and whether HCAP patients have improved outcomes when treated with empiric broad‐spectrum antibiotics. METHODS: A retrospective cohort study at 488 US hospitals from July 2007 to November 2011. Patients who met criteria for HCAP were included. Guideline‐concordant antibiotics were assessed based on guideline recommendations. We assessed changes in hospital rates of concordant antibiotic use over time and their correlation with outcomes. RESULTS: Among 149, 963 patients with HCAP, 19.6% received fully guideline‐concordant antibiotics, 21.7% received partially concordant antibiotics, and 58.9% received discordant antibiotics. Guideline concordance increased over time. Rates of fully or partially concordant antibiotics varied across hospitals (median 36.4%; interquartile range 25.8%‐49.1%). Among patients who received discordant antibiotics, 81.5% were treated according to community‐acquired pneumonia (CAP) guidelines. On average, the rate of guideline concordance increased by 2.2% per 6‐month interval, while hospital level rates of mortality, excess length of stay, and progression to respiratory failure did not change. CONCLUSIONS: In this large, nationally representative cohort, only 1 in 5 patients with risk factors for HCAP received treatment that was fully in accordance with guidelines, and many received CAP therapy instead. At the hospital level, increases in the use of concordant antibiotics were not associated with declines in mortality, excess length of stay, or progression to respiratory failure.